Improvement Managerial Ability Manager of Cendekia Lasem Vocational High School Unit Production - tahwin, muhammad (Universitas Islam Nahdlatul Ulama Jepara, 2022)
As a partner in this community dedication is the Unit Production of Cendekia Lasem Vocational High School. The problems faced by partner are (1) Low business motivation, (2) Not being able to arrange a business plan, and (3) Not having the ability to manage finances. Thus the implementation of this dedication Program is to improve the managerial ability of Cendekia Lasem Vocational School Unit Production Manager. The implementation methods used are training and mentoring. The results of the activity are (1) partners show a positive attitude to face opportunities and challenges in developing unit production, (2) partners are able to arrange a business plan so that they have an overview of the business to be carried out including activity plans to achieve business goals, and (3) partners are able to arrange financial report based Android so it can be easy to make financial reports.Â